UPAYA MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN PKN MELALUI MODEL âPERTANYAAN TERBUKAâ - Ramelan, - (Universitas Islam Darul Ulum, 2016)
Civics is one of the subjects that have a role in shaping the character of students, but lately other than the application of positive values that exist in the material subject of Civics feel to have fragile and has no meaning, it is proven values obtained by the students still less than satisfactory, as academic, students also flagged an interest in learning. In this study conducted in two cycles, each cycle consisting of four stages: planning, execution, observation and reflection. This action research results are as follows: in the first cycle of observation results sheet student interest average percentage is 63.5% and the average value of daily tests 68.03, while in the second cycle of observation sheet student interest Average percentage 73.67 % and the average daily value of replications 81.29. It can be concluded that the application of cooperative learning can increase interest and student achievement in the subject of Civics.